Question and Answers Forum

All Questions      Topic List

UNKNOWN Questions

Previous in All Question      Next in All Question      

Previous in UNKNOWN      Next in UNKNOWN      

Question Number 53693 by gunawan last updated on 25/Jan/19

 ∫_( 0) ^(π/2)  ((x+sin x)/(1+cos x)) dx =

π/20x+sinx1+cosxdx=

Commented by maxmathsup by imad last updated on 25/Jan/19

let I =∫_0 ^(π/2)   ((x+sinx)/(1+cosx)) ⇒I =∫_0 ^(π/2)   (x/(1+cosx))dx +∫_0 ^(π/2)   ((sinx)/(1+cosx))dx but  ∫_0 ^(π/2)   ((sinx)/(1+cosx))dx =−∫_0 ^(π/2)   (((cosx)^, )/(1+cosx)) dx =−[ln∣1+cosx∣]_0 ^(π/2) =−(−ln(2))=ln(2)  ∫_0 ^(π/2)   (x/(1+cosx))dx =(1/2) ∫_0 ^(π/2)   (x/(cos^2 ((x/2))))dx =(1/2) ∫_0 ^(π/2) x(1+tan^2 ((x/2))dx but  ∫_0 ^(π/2) x(1+tan^2 ((x/2)))dx =_((x/2)=t)     ∫_0 ^(π/4)  (2t)(1+tan^2 t)(2)dt  =4 ∫_0 ^(π/4)  t(1+tan^2 t)dt   by parts u=t and v^′ =1+tan^2 t ⇒  ∫_0 ^(π/4)  t(1+tan^2 t)dt =[t tant]_0 ^(π/4)  −∫_0 ^(π/4)  tant dt  =(π/4) + ∫_0 ^(π/4)   ((−sint)/(cost)) dt =(π/4) +[ln∣cost∣]_0 ^(π/4)  =(π/4) +ln((1/(√2)))=(π/4) −(1/2)ln(2) ⇒  ∫_0 ^(π/2) x(1+tan^2 ((x/2)))dx =π−2ln(2) ⇒  I =ln(2) +(1/2)(π−2ln(2)) ⇒ I =(π/2) .

letI=0π2x+sinx1+cosxI=0π2x1+cosxdx+0π2sinx1+cosxdxbut0π2sinx1+cosxdx=0π2(cosx),1+cosxdx=[ln1+cosx]0π2=(ln(2))=ln(2)0π2x1+cosxdx=120π2xcos2(x2)dx=120π2x(1+tan2(x2)dxbut0π2x(1+tan2(x2))dx=x2=t0π4(2t)(1+tan2t)(2)dt=40π4t(1+tan2t)dtbypartsu=tandv=1+tan2t0π4t(1+tan2t)dt=[ttant]0π40π4tantdt=π4+0π4sintcostdt=π4+[lncost]0π4=π4+ln(12)=π412ln(2)0π2x(1+tan2(x2))dx=π2ln(2)I=ln(2)+12(π2ln(2))I=π2.

Answered by tanmay.chaudhury50@gmail.com last updated on 25/Jan/19

∫_0 ^(π/2) (x/(1+cosx))dx−∫_0 ^(π/2) ((d(1+cosx))/(1+cosx))  ∫_0 ^(π/2) x×(1/(2cos^2 (x/2)))−∫_0 ^(π/2) ((d(1+cosx))/(1+cosx))  now...  ∫xsec^2 (x/2)dx  x×((tan(x/2))/(1/2))−∫[(dx/dx)∫sec^2 (x/2)dx]dx  =2xtan(x/2)−∫((tan(x/2))/(1/2))dx  =2xtan(x/2)−2lnsec(x/2)  so  (1/2)∫_0 ^(π/2) xsec^2 (x/2)−∫_0 ^(π/2) ((d(1+cosx))/(1+cosx))  (1/2)∣2xtan(x/2)−2lnsec(x/2)∣_0 ^(π/2) −∣ln(1+cosx)∣_0 ^(π/2)   ={((π/2)tan(π/4)−lnsec(π/4))−(0×tan(0/2)−lnsec0)}−{ln(1+0)−ln(1+1)}  ={((π/2)×1−ln(√2) )−(0−0)}−{0−ln2}  =(π/2)−(1/2)ln2+ln2  =(π/2)+(1/2)ln2  pls check steps...

0π2x1+cosxdx0π2d(1+cosx)1+cosx0π2x×12cos2x20π2d(1+cosx)1+cosxnow...xsec2x2dxx×tanx212[dxdxsec2x2dx]dx=2xtanx2tanx212dx=2xtanx22lnsecx2so120π2xsec2x20π2d(1+cosx)1+cosx122xtanx22lnsecx20π2ln(1+cosx)0π2={(π2tanπ4lnsecπ4)(0×tan02lnsec0)}{ln(1+0)ln(1+1)}={(π2×1ln2)(00)}{0ln2}=π212ln2+ln2=π2+12ln2plschecksteps...

Terms of Service

Privacy Policy

Contact: info@tinkutara.com